2015
DOI: 10.1108/apjml-12-2014-0180
|View full text |Cite
|
Sign up to set email alerts
|

The impact of territory of origin on product authenticity perceptions

Abstract: Purpose -The purpose of this paper is to demonstrate the importance of territory of origin (TOO) associations for consumers' perception of product authenticity and empirically tests the chain of effects, from TOO associations to perceived authenticity, and to consumers' self-brand connections. Design/methodology/approach -An experimental method and a partial least square approach were adopted. Hypotheses were tested on data collected across 665 Chinese consumers. Findings -Results demonstrate that TOO exerts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
(67 reference statements)
0
25
0
Order By: Relevance
“…Authenticity is the individual's opinion of what is true, real or genuine (Beverland, 2005; Grayson and Martinec, 2004; Southworth and Ha-Brookshire, 2016). Authenticity has two approaches that are emphasized in the literature: (1) an objective approach that helps the consumers by providing information to assess the authenticity in a brand (Beverland, 2005; Grayson and Martinec, 2004; Zhang and Merunka, 2015). (2) In the subjective approach, authenticity is created as being influenced by consumers’ interests, knowledge, personal tastes and interpretation (Napoli et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authenticity is the individual's opinion of what is true, real or genuine (Beverland, 2005; Grayson and Martinec, 2004; Southworth and Ha-Brookshire, 2016). Authenticity has two approaches that are emphasized in the literature: (1) an objective approach that helps the consumers by providing information to assess the authenticity in a brand (Beverland, 2005; Grayson and Martinec, 2004; Zhang and Merunka, 2015). (2) In the subjective approach, authenticity is created as being influenced by consumers’ interests, knowledge, personal tastes and interpretation (Napoli et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As previously stated, several empirical studies support the opinion that a brand’s origin counts when consumers decide whether to buy a product presented as a particular brand (Diamantopoulos et al , 2011; Winit et al , 2014; Zhang and Merunka, 2015; Haliakias et al , 2016; Kim and Park, 2017). For instance, when looking for the underlying reason for the importance of global brands, Pecotich and Ward (2007) found that developed countries such as Japan, Germany and the USA are associated by global consumers with high-value brands and consequently high-quality products, whereas newly developing nations with a lower level of recognition are associated with poorer-quality products.…”
Section: Literature Backgroundmentioning
confidence: 63%
“…The concept of authenticity defined as the interpretation of the genuineness and increased appreciation of the tourism object (Chambers, 2009) plays a significant role in destination competitiveness (Ramkissoon and Uysal, 2010, 2011). Lin et al (2017) and Zhang and Merunka (2015) indicate that authenticity can serve as a boundary condition on customer evaluations and behaviors. Gaytán (2008, p. 315) argues that “consumption serves as a means through which authenticity becomes a measure of the quality, efficacy and legitimacy of one’s experience in a particular setting.” Lalicic and Weismayer (2017) focus on whether the authenticity of perceptions of whether to stay or not to stay at a hotel feel like “living the local life.” Birinci et al (2018) propose that perceived authenticity plays a key role in customer decision-making processes when determining accommodation and repurchase intentions.…”
Section: Theory and Hypothesesmentioning
confidence: 99%